Class and Gender in Older People Care in Rural Yogyakarta - Larastiti, Ciptaningrat; Widjaya, Hanny; White, Ben (Humaniora, 2024)
This article explores care arrangements for older people in rural Yogyakarta, comparing and contrasting the experiences of older people in three agrarian classes: significant landowners, petty commodity producers and ‘classes of labour’. The study was conducted in two villages in Kulon Progo and Sleman Regencies. Qualitative interviews, observations, life histories and information on the changing social and economic contexts are used to analyse older people’s roles in social reproduction, the dynamics of intergenerational dependency, and the practicesof older-people care. We found great variation in the age at which engagement in productive and reproductive work declines and people enter the state of dependency. Older people may be receivers, or providers of care for younger dependents. As older people live longer, complex tri- and even quadri-generational care arrangements become more common. Class, gender and intergenerational relations shape care relations and practices. State and community programmes for older people, when functioning properly, can be of great importance to poorer households,even though the access is uneven and they do not always match older people’s care needs. Commodified (purchased) care provision is found in some relatively prosperous households, but rarely in the ‘classes of labour’, the landless and near-landless peasants, and worker households that make up the majority of the population.